Broadening the Scope of Diversity Management : Strategic Implications in the Case of the Netherlands - Glastra, Folke; Meerman, Martha; Schedler, Petra; de Vries, Sjiera (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2000)
An analysis of theories and practices of diversity management, as illustrated in the case of the Netherlands, shows that they are too narrowly focused on redressing imbalances experienced by ethnic minorities and bridging cultural differences between majorities and ethnic minorities in the workplace. Agencies in the field of diversity management have fallen back on a limited and standardized stock of methods that ignore the specificity of organizational dynamics and largely operate in isolation from existing equity policies. The influence of diversity management has thus remained quite superficial. A contextual approach would broaden both the body of thought and the repertory of methods of diversity management, and strengthen its political and social relations. Such an approach would respond to its most challenging tasks: fostering social justice, enhancing productivity, and breaking the circle that equates cultural difference with social inequality